Pengungkapan Intellectual Capital, Reputasi Underwriter dan IPO Underpricing - Zulhawati Zulhawati (Jurnal Manajemen dan Bisnis Indonesia, 2014)
This study examines the effect of Intellectual Capital Disclosure and Underwriter Reputation to IPO Underpricing the company public on Indonesia Stock Exchange 2007-2012. The Results of research on the observation period there was 80% of companies experiencing IPO underpricing. Underpricing phenomenon is deliberately done to get the attention of the company's stock price increases in the first day listing or may occur due to information asymmetries between issuers and underwriters among and investors who have information about the issuer's prospects. Information asymmetry can be reduced by presenting financial information and non-financial information in the prospectus, one of non- financial information to be presented is intellectual capital. Information about the underwriter's reputation is also required by investors as a measure of financial information that is relevant and reliable. The results of multiple regression statistical test indicates that intellectual capital disclosure and underwriter reputation negatively affect the level of underpricing. This suggests that the higher intellectual capital disclosure can reduce IPO underpricing, as well as a good underwriter reputation can reduce IPO underpricing. Keywords: IPO underpricing, intellectual capital disclosure, underwriter reputation, infor-mation asymmetries